Citra Korban Kekerasan Seksual Okezone Berlandaskan Kode Etik Jurnalistik Pasal 4 dan 5 - Zulva Azhar Aulia Ulhaq; Indrya Mulyaningsih; Itaristanti (Widyantara, 2023)
Based on the Press Council Journalism Code of Ethics articles 4 and 5, this research aims to determine the media's bias towards the victims or perpetrators of violence. This research is a form of qualitative descriptive research that described data systematically, in detail and in depth. The data comes from three West Java Okezone online news stories about sexual violence throughout 2020. The pay close attention and Take Note technique used to collect the data, which then presented using the technique matching. The data analysed through critical discourse analysis with Sara Mills' analytical point of view, which considers into account of the subject-object of the discourse along with the opinions of the author and the reader of the article. The results of this research divided into two, namely 1) the West Java Okezone online news takes the side of victims of violence, not the perpetrators 2) the West Java Okezone online news applies the Journalistic Code of Ethics Articles 4 and 5. Kode Etik Jurnalistik Dewan Pers pasal 4 dan 5, penelitian ini bertujuan untuk mengetahui keberpihakan media, kepada korban atau pelaku kekerasan. Penelitian ini merupakan bentuk penelitian deskriptif kualitataif yang mendeskripsikan data secara sistematis, rinci, dan mendalam. Data bersumber dari tiga berita daring Okezone Jabar tentang kekerasan seksual sepanjang tahun 2020. Data diperoleh menggunakan Teknik Simak dan catat lalu disajikan menggunakan teknik padan. Data akan dianalisis melalui Analisis Wacana Kritis dengan pandangan Analisis Sara Mills yang di dalamnya terdapat subjek-objek wacana serta pandangan penulis dan pembaca wacana. Hasil penelitian ini terbagi menjadi dua yaitu 1) berita daring Okezone Jabar berpihak kepada korban kekerasan, bukan pelaku 2) berita daring Okezone Jabar menerapkan Kode Etik Jurnalistik Pasal 4 dan 5.